2020
DOI: 10.1016/j.vaccine.2020.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of peptides from Plasmodium vivax circumsporozoite protein

Abstract: Highlights Short repeat-region peptides from PvCSP on a VLP protect against malaria. The AGDR tetramer from PvCSP VK210 can, on a VLP, also protect against malaria. Full-length PvCSP is much less protective as a vaccine than truncated PvCSP. Region I and II peptides confer no protection against malaria presented on a VLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In previous studies, we generated two chimeric P. berghei parasites ( Pb-Pv CSP210 and Pb-Pv CSP247) that express the full-length VK210 and VK247 variants of P. vivax CSP on the spz surface 25 . These parasites have been used to analyze protective efficacy in mice immunized with different vaccine candidates targeting Pv CSP with an immunization-challenge mouse model 41 43 . To analyze protective immune responses induced by the two recombinant proteins NLP-CSP CT or NLP-CSP R against not only the VK210 and VK247 repeats but also against the P. vivax -like variant, we generated a third chimeric P. berghei parasite that expressed the Pv CSP- P. vivax -like protein in spz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we generated two chimeric P. berghei parasites ( Pb-Pv CSP210 and Pb-Pv CSP247) that express the full-length VK210 and VK247 variants of P. vivax CSP on the spz surface 25 . These parasites have been used to analyze protective efficacy in mice immunized with different vaccine candidates targeting Pv CSP with an immunization-challenge mouse model 41 43 . To analyze protective immune responses induced by the two recombinant proteins NLP-CSP CT or NLP-CSP R against not only the VK210 and VK247 repeats but also against the P. vivax -like variant, we generated a third chimeric P. berghei parasite that expressed the Pv CSP- P. vivax -like protein in spz.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the use of transgenic parasites in the study of CSP-based vaccine formulations for the pre-erythrocytic phase of infection has allowed the analysis of functional inhibition of the exogenous CSP, expressed in replacement of the endogenous protein. Following this strategy, chimeric P. berghei parasites expressing the P. vivax CSP variants VK210 and VK247 were used to determine the protective efficacy of vaccine formulations consisting of viral vectors carrying P. vivax CSP alleles 25 , 41 43 . In this study, we generated for the first time a chimeric P. berghei parasite line expressing the third Pv CSP variant, Pv CSP- P. vivax -like.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the potential of this extended region as a vaccine candidate and should be the focus of further study; although the efficacy conferred by individual peptides is low, extending vaccination to include all (and only) the disordered region of TRAP may be more protective, focusing the response on neutralising targets and away from immunogenic but antigenically non-protective regions of TRAP. It will also be of interest to try combining the immunodominant CD8 + T-cell epitope from PvTRAP with protective PvCSP repeat peptides 27 on a single immunodominant antigen, although research has shown that much higher doses of Qβ are required 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In areas where drug resistance has been identi ed 27 , artemisinin combination therapy (ACT) is recommended, but the continuous increase and spread of resistance against anti-malarial drugs is of great concern in order to achieve the goal of eliminating malaria successful 28,29 . Moreover, VMP001, an advanced P. vivax' CSP-based malaria vaccine, has been reported to offers only lowest rate of protection against vivax malaria in humans 34 . There is currently no successful vaccine against malaria and only a small number of vaccines against P. vivax have been tested to date.…”
Section: Discussionmentioning
confidence: 99%
“…CSP has been identi ed to play a vital role in the maturation of sporozoite in the mosquito vector 31,32 . Plasmodium species conserve the CSP structure being an immunodominant B-cell epitope comprising of a central tandem portion anked by two non-repetitive domains containing proteolytic cleavage site and the thrombospondin repeat (TSR) at C-terminus 7,31,33 The protective e cacy of small peptide of allelic variants VK210 and VK247 of P. vivax CSP (PvCSP) has been reported as Qβ-peptide vaccine in order to provide minimal immunity for malaria 34 . The putative CSP of P. vivax plays a key role in coordinating protein degradation in P. vivax and can be used as a potential vaccine target, but extensive study needs to be carried out on this 30 .…”
Section: Introductionmentioning
confidence: 99%